2018
DOI: 10.1063/1.5025509
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of floating-gate memory device with thiolate-protected gold and gold-palladium nanoclusters

Abstract: The floating-gate memory characteristics of thiolate-protected gold (Au:SR) and palladium doped Au (AuPd:SR) nanoclusters, Au25(SR)18, Au24Pd(SR)18, and Au38(SR)24 (R = C12H25), were investigated by capacitance-voltage (C–V) measurements in vacuum. Monolayer films of Au:SR nanoclusters were formed as floating-gate memory layers on p-type Si substrates by the Langmuir-Schaefer method with surface pressure − area (π-A) isotherm measurements. A fluoropolymer (CYTOP, ∼15 nm thick) was spin-coated on top to form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…As shown in Figure 14 (Figure 16(a)) 148,286,507,568,603,706,721,767,768,791,795,813,826 and co-reduction method (Figure 16(b)). 43,58,174,219,222,241,262,300,305,311,346,356,431,536,587,601,614 In this study, we found that the isomer distribution also depends on the standing time in solution. As an example, Figure 17 shows the time dependence of the EI chromatogram of Au 25¹x Ag x (SC 4 H 9 ) 18 (x = 24) synthesized by the metalexchange method (Figure 16(a)).…”
Section: Dependence Of Isomer Distribution On Preparative Conditionsmentioning
confidence: 50%
See 1 more Smart Citation
“…As shown in Figure 14 (Figure 16(a)) 148,286,507,568,603,706,721,767,768,791,795,813,826 and co-reduction method (Figure 16(b)). 43,58,174,219,222,241,262,300,305,311,346,356,431,536,587,601,614 In this study, we found that the isomer distribution also depends on the standing time in solution. As an example, Figure 17 shows the time dependence of the EI chromatogram of Au 25¹x Ag x (SC 4 H 9 ) 18 (x = 24) synthesized by the metalexchange method (Figure 16(a)).…”
Section: Dependence Of Isomer Distribution On Preparative Conditionsmentioning
confidence: 50%
“…The formation of Au 24 Pd clusters with the use of hydrophobic ligands has been reported. 43,219,262,300,369,431,445,452,614,653,672,702,706,708,709,711,722,731,738,791,795,827,828,915917,947 However, we believe that this is the first observation of Au 14 Pd, Au 17 Pd, Au 16 Pd 2 , and Au 28 Pd. These results demonstrate that alloy clusters in which part of Au is replaced by Pd can be synthesized for the Au n (SG) m clusters.…”
Section: Chemical Compositions Of Gold Clustersmentioning
confidence: 57%
“…From the viewpoint of the water contact angle, it is ∼38° for the Si substrate, which is an intermediate value between the Au(111) and F-SAM. Although the microscopic transfer mechanism is unclear at present, the Si substrate seems ideal for fabricating a Au n :SC12 monolayer on its surface with LS transfer . Note that, also for Au 25 :SC12 on F-SAM, the temperature dependence of I ip / I op at 2960 cm –1 is analyzed in the Supporting Information (see Note S6 and Figures S11 and S12).…”
Section: Resultsmentioning
confidence: 99%
“…Monolayers of Au n :SC12 and Au n :SC2Ph were fabricated using the Langmuir–Blodgett method: ∼0.2 mg/mL solution of each NC was prepared in chloroform (CHCl 3 ) and the solution was carefully spread onto ultrapure water in a trough (KSV NIMA Small, Biolin Scientific), with subsequent evaporation of the solvent and compression of the NCs into a Langmuir film. , To form a monolayer, compression was stopped at the minima of the first or second derivative of the surface pressure–area (π– A ) isotherm, which is typically 30, 20, and 5 mN/m for Au 25 :SC12, Au 38 :SC12, and Au 144 :SC12, respectively, and around 5 mN/m for Au n :SC2Ph (some π– A isotherms are shown in the Supporting Information (Figures S1 and S2)). Then, each monolayer made contact with the surface of a fresh Au(111) single crystal to be transferred based on the Langmuir–Schaefer (LS) horizontal liftoff method .…”
Section: Methodsmentioning
confidence: 99%
“…To form a one-dimensional (1D) arrangement of metal NCs, templates [ 109 , 110 ] and host–guest interactions [ 111 ] are extremely effective. Two-dimensional (2D) and three-dimensional (3D) arrays of metal NCs can be fabricated by Langmuir–Blodgett [ 112 ] and alternate adsorption methods. There are many reports in which metal NCs are arranged in one, two, and three dimensions by using these methods.…”
Section: Introductionmentioning
confidence: 99%